2014
DOI: 10.3233/jhd-140110
|View full text |Cite
|
Sign up to set email alerts
|

Disease Modifying Potential of Glatiramer Acetate in Huntington's Disease

Abstract: Background: Deficiencies in brain-derived-neurotrophic-factor have been implicated in the pathogenesis of Huntington's disease (HD). Objective: Glatiramer acetate, an FDA-approved drug used for the treatment of multiple sclerosis, has been shown to increase brain-derived-neurotrophic-factor levels in immune cells; hence, we investigated whether it could have similar effects in striatal cells. Methods: Wild-type and HD striatal cells were treated with glatiramer acetate for 48 hrs. HD transgenic and wild-type m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…GA has been used for the treatment of relapsing-remitting multiple sclerosis for more than two decades. Over the last decade, its effects have been found to be beneficial in mouse models of disorders with a prominent neuroinflammatory component such as ischemic injury, glaucoma and Huntington's disease (Bakalash et al, 2005;Corey-Bloom et al, 2014;He et al, 2014;Reick et al, 2016;Cruz et al, 2018). In agreement with what has been previously reported in other models of neurodegeneration (Rentsendorj et al, 2018;Doustar et al, 2020), we found that GA improved cognitive performance in 3xTg AD mice.…”
Section: Discussionsupporting
confidence: 91%
“…GA has been used for the treatment of relapsing-remitting multiple sclerosis for more than two decades. Over the last decade, its effects have been found to be beneficial in mouse models of disorders with a prominent neuroinflammatory component such as ischemic injury, glaucoma and Huntington's disease (Bakalash et al, 2005;Corey-Bloom et al, 2014;He et al, 2014;Reick et al, 2016;Cruz et al, 2018). In agreement with what has been previously reported in other models of neurodegeneration (Rentsendorj et al, 2018;Doustar et al, 2020), we found that GA improved cognitive performance in 3xTg AD mice.…”
Section: Discussionsupporting
confidence: 91%
“…Evaluation of serum and CNS of GA-treated mice showed increased levels of the anti-inflammatory cytokine IL-10 and brain-derived neurotrophic factor (BDNF), both of which are produced by activated Th2 cells [147149]. In addition, not only has GA been effective in decreasing pathology in models of experimental autoimmune encephalomyelitis, but it has also shown benefits in Huntington’s disease models [149, 150]. GA use in amyloidogenic mouse models successfully reduced plaque load; however, the effects of GA on tau pathology remain untested [141143].…”
Section: Introductionmentioning
confidence: 99%
“…K1127 (Kemptide acetate salt) was not employed for the fourth screening because a computer search suggested a possible similarity between Kemptide acetate salt and glatiramer acetate (Copaxone), which had been tested in an HD mouse model (N171-82Q transgenic mice) and has been previously reported to ameliorate the metabolic activity and parameters of motor function, including jumping counts and stereotypic counts 33 . However, a detailed search ruled out a direct relationship between Kemptide acetate salt and these results.…”
Section: Resultsmentioning
confidence: 99%